(3cGed GdUfGYI aj GdaQhSjI hGdTLGYIs - (3GdnqQnqeGM; eMeO Hf dGLjf Hf YHO Gddg GdMSGej,J (B780 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CPgH YfG GdMRf Ef QHfG dZahQ TchQ hdi GdMeO hGgdg eSJNdU GdMeO dfaSg s
(3BNQgG (B:s
(3aMjfFP JLQ Ydjg aQSc aJWYfg CefkG ef QeMg Ke JNQL ef SQjYkG hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B15 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B164s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B_ (3ecfGS (B(10/ 1) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs